2020
DOI: 10.4187/respcare.07500
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Big Data During Mechanical Ventilation in the ICU

Abstract: The electronic health record allows the assimilation of large amounts of clinical and laboratory data. Big data describes the analysis of large data sets using computational modeling to reveal patterns, trends, and associations. How can big data be used to predict ventilator discontinuation or impending compromise, and how can it be incorporated into the clinical workflow? This article will serve 2 purposes. First, a general overview is provided for the layperson and introduces key concepts, definitions, best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…However, due to the influence of many factors, MV will inevitably lead to adverse postoperative outcomes, such as weaning difficulties caused by serious respiratory fatigue, spontaneous respiratory arrest, and prolonged treatment time [ 17 ]. Referring to the previous data, we found that DD was one of the important reasons for the difficulty and failure of weaning [ 18 ]. Therefore, active prevention and treatment of DD is of great significance to help patients recover as soon as possible and improve postoperative outcomes.…”
Section: Resultssupporting
confidence: 63%
“…However, due to the influence of many factors, MV will inevitably lead to adverse postoperative outcomes, such as weaning difficulties caused by serious respiratory fatigue, spontaneous respiratory arrest, and prolonged treatment time [ 17 ]. Referring to the previous data, we found that DD was one of the important reasons for the difficulty and failure of weaning [ 18 ]. Therefore, active prevention and treatment of DD is of great significance to help patients recover as soon as possible and improve postoperative outcomes.…”
Section: Resultssupporting
confidence: 63%
“…Smallwood [16] emphasized using a big data technique during MV in the ICU because many aspects in the ICU are not well informed by high-quality, large, randomized controlled trials (RCTs), and high-variability among providers. It is not evitable due to that individual patient data is complex.…”
Section: Related Workmentioning
confidence: 99%
“…Meanwhile, MLA's indirect MV intervention is primarily used to predict health outcomes and evaluate clinical interventions. Because there is no need to intervene in the MV directly, retrospective studies are a good way to evaluate direct MV intervention by MLA in a safe manner [16]. The existing trends of MLA application studies demonstrate the feasibility and the promising of MLA as a direct MV intervention.…”
Section: Research Question 1: How Does the Integration Of ML And Vm C...mentioning
confidence: 99%